Mechanical stretch induces hair regeneration through the alternative activation of macrophages - Chu, Szu-Ying; Chou, Chih-Hung; Huang, Hsien-Da; Yen, Meng-Hua; Hong, Hsiao-Chin; Chao, Po-Han; Wang, Yu-Hsuan; Chen, Po-Yu; Nian, Shi-Xin; Chen, Yu-Ru; Liou, Li-Ying; Liu, Yu-Chen; et al. (Nature communications, 2019)
Tissues and cells in organism are continuously exposed to complex mechanical cues from the environment. Mechanical stimulations affect cell proliferation, differentiation, and migration, as well as determining tissue homeostasis and repair. By using a specially designed skin-stretching device, we discover that hair stem cells proliferate in response to stretch and hair regeneration occurs only when applying proper strain for an appropriate duration. A counterbalance between WNT and BMP-2 and the subsequent two-step mechanism are identified through molecular and genetic analyses. Macrophages are first recruited by chemokines produced by stretch and polarized to M2 phenotype. Growth factors such as HGF and IGF-1, released by M2 macrophages, then activate stem cells and facilitate hair regeneration. A hierarchical control system is revealed, from mechanical and chemical signals to cell behaviors and tissue responses, elucidating avenues of regenerative medicine and disease control by demonstrating the potential to manipulate cellular processes through simple mechanical stimulation. Mechanical stimulation is known to affect cell proliferation, differentiation, and regeneration. Here, the authors demonstrate that stretching mouse skin recruits macrophages and polarizes them into M2 cells that facilitate hair regeneration through the release of growth factors, including HGF and IGF-1